2022
DOI: 10.1136/bmjopen-2020-047555
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves sleep quality in older adults: a protocol for a systematic review and meta-analysis

Abstract: IntroductionSleep disturbance is a common problem among the elderly and is associated with physical and mental health. Exercise has been reported as an alternative therapeutic strategy for people with sleep disturbances. However, this topic has not been systematically reviewed for older adults. This study was conducted to provide a protocol to systematically evaluate the effects of exercise on sleep quality in the elderly.Methods and analysisAn electronic search of the PubMed, Embase and Cochrane Library datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…According to Zhang et al 22 , sleep disorders are risk factors for major health problems, including systemic arterial hypertension, diabetes, cancer, mental and cognitive disorders. In addition to offering health benefits, an intervention based on regular exercise reduces the risk of mortality and chronic diseases, and can be considered a low-cost alternative 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zhang et al 22 , sleep disorders are risk factors for major health problems, including systemic arterial hypertension, diabetes, cancer, mental and cognitive disorders. In addition to offering health benefits, an intervention based on regular exercise reduces the risk of mortality and chronic diseases, and can be considered a low-cost alternative 22 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhang et al 22 , sleep disorders are risk factors for major health problems, including systemic arterial hypertension, diabetes, cancer, mental and cognitive disorders. In addition to offering health benefits, an intervention based on regular exercise reduces the risk of mortality and chronic diseases, and can be considered a low-cost alternative 22 . We observed that the PG volunteers had a higher prevalence of good sleep quality compared to the NPG, constituting data which corroborate a study performed with women over 60 years of age who participated in a regular physical exercise program and presented better levels of sleep quality 23 .…”
Section: Discussionmentioning
confidence: 99%